Diseño de una PCH para la generación de energía eléctrica aprovechando el sistema de abastecimiento de agua a Riohacha distrito turístico y cultural (2022)
This degree work proposes the design of a SHP for the generation of electric energy in a point of the water supply network of Riohacha, which allows the recovery of hydroelectric energy and enables the supply of electric energy to the surrounding Wayuu communities. The calculation of the design of the SHP resulted in a specific number of revolutions Ns of 86.87 that allows to take as a reference the range of values of the different turbines, for this case the value of Ns is between 50 and 150, allowing to select a slow Francis type turbine. The PCH can satisfy the daily consumption of each household located in 1634 W/h, the energy generation is 240 kW/h. The work was developed under the type of descriptive research proposed in three phases: energy recovery systems in hydraulic networks, design of a hydraulic system and evaluation of the system.